Present‐Day Three‐Dimensional Crustal Deformation Velocity of the Tibetan Plateau Due to Multi‐Component Land Water Loading - Jiashuang Jiao; Yuanjin Pan; Ding Ren; Xiaohong Zhang (Geophysical Research Letters)
Abstract Quantitative understanding of the land water loading is a prerequisite to the construction of reliable tectonic deformation velocity field in the Tibetan Plateau (TP). Here, for the first time, we image the three‐dimensional crustal loading deformation velocity field of each land water component in the TP. Our results reveal that the loading signal strength of the six land water components ranks from largest to smallest as groundwater, glacier, lake, soil water, permafrost, and snow, with the maximum vertical velocity close to ±1.60 mm/yr and the maximum horizontal velocity exceeding 0.40 mm/yr. All land water components can achieve a strong enough vertical loading velocity exceeding the present‐day Global Positioning System (GPS) velocity at some sites. But for horizontal loading, apparent impacts are only from glacier, lake and groundwater, however, are very limited, with the absolute ratio of loading velocity to GPS velocity being smaller than 5% at almost all the sites.